Land and agronomic potential for biofuel production in Southern Africa - Graham von Maltitz; Marna van der Merwe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The Southern African region, from a purely biophysical perspective, has huge potential for biofuel production, especially in Mozambique and Zambia. Although many of the soils are sandy and acidic, with careful management and correct fertilization, they should be highly productive. We suggest that sugarcane is the crop most easily mobilized for biofuel. A number of other crops, such as sweet sorghum, cassava, and tropical sugar beet, have good potential but will need further agronomic and processing technology investigations.
Keywords: Q40; Q42; Q16; 330; biofuel; Southern Africa; production potential; crop yields; sugarcane; cassava